Moral education :a critical analysis - Darfrina Allnia, Allok (University Malaysia Sarawak, (UNIMAS), 2005)
This study aims to examine critically the central thesis of moral education. The objectives of this study are to explain the definition of Moral Development and Moral Education, to elaborate on two models of morality: The Evolutionary Model of Morality and The Religious Model of Morality and to understand Piaget's Moral Development Theory and Kohlberg's Moral Development Theory. Specifically, this study is done to see in depth how Moral Education and Moral Development affect one's personality fonnation, to see how religion and moral development is connected to each other and to give clear comparison between two models of morality: The Evolutionary Model and The Religious Model. This study has generally accomplished the objectives set out. The major finding is that moral education and moral education are so much related to each other. Moral development that occurred and moral education that one's received detennine their personality. It is hoped that the thesis has contributed something to the literature.